Expanding Access to Halal Food SME Partnerships Using the 5W+1H in Tangerang Regency - Devi Nadia; Anni Rohimah (Yayasan Darussalam Patalassang, 2026)
This study aims to identify obstacles and solutions for expanding access to partnerships for Micro, Small, and Medium Enterprises (MSMEs) in the halal food sector in Tangerang Regency using the 5W+1H approach. Data collected from 39 MSMEs revealed that only 5.13% had complete partnership records. A descriptive qualitative approach was employed through interviews with directors of supporting institutions, deputy advisors, academics, and MSME practitioners. The findings revealed that the main challenges include limited knowledge of halal standards, insufficient access to technology and digital marketing, and a lack of partnership networks. Recommendations include intensive mentoring for six months, the implementation of Orgaware, and digital marketing strategies. The 5W+1H approach is effective in mapping issues and formulating solutions aligned with Sustainable Development Goal (SDG) 8.